Scientific astrophotography : how amateurs can generate and use professional imaging data - Hubbell, Gerald R. (Patrick Moore's Practical Astronomy Series, 2013)
Scientific Astrophotography is a work for those amateur astronomers looking for new challenges, once they have mastered visual observing and the basic imaging of various astronomical objects. It is a wonderful reference for scientifically-inclined observers who want to learn the fundamentals of astrophotography with a firm emphasis on the discipline of scientific imaging. This book is a wealth of information and a distillation of ideas presented by a diverse set of sources and based on the most recent techniques, equipment, and data available. It also includes numerous exercises for the reader, to maximize the success and minimize the frustration inherent in the pursuit of this specific craft. Scientific Astrophotography is perfect for any amateur astronomer who wants to go beyond just the process of making beautiful images and actually contribute to the science of astronomy! "...Gerald Hubbell's new book, Scientific Astrophotography, is the perfect companion for anyone dipping their toe into the digital imaging realm for the first time. The author answers all the questions people have when starting out, such as how do I get the most bang for my buck, and how do I select the right CCD for my telescope?" - Mike Simonsen, American Association of Variable Star Observers